A Comparative Study of Glasgow Coma Scale and Full Outline of Unresponsiveness Scores for Predicting Long-Term Outcome After Brain Injury. Issue 4 (July 2016) - McNett, Molly M.; Amato, Shelly; Philippbar, Sue Ann
Abstract : ABSTRACT: Purpose: The aim of this study was to compare predictive ability of hospital Glasgow Coma Scale (GCS) scores and scores obtained using a novel coma scoring tool (the Full Outline of Unresponsiveness [FOUR] scale) on long-term outcomes among patients with traumatic brain injury. Preliminary research of the FOUR scale suggests that it is comparable with GCS for predicting mortality and functional outcome at hospital discharge. No research has investigated relationships between coma scores and outcome 12 months postinjury.Methods: This is a prospective cohort study. Data were gathered on adult patients with traumatic brain injury admitted to urban level I trauma center. GCS and FOUR scores were assigned at 24 and 72 hours and at hospital discharge. Glasgow Outcome Scale scores were assigned at 6 and 12 months.Results: The sample size was n = 107. Mean age was 53.5 ( SD = ±21, range = 18–91) years. Spearman correlations were comparable and strongest among discharge GCS and FOUR scores and 12-month outcome ( r = .73, p < .000; r = .72, p < .000). Multivariate regression models indicate that age and discharge GCS were the strongest predictors of outcome. Areas under the curve were similar for GCS and FOUR scores, with discharge scores occupying the largest areas.Conclusion: GCS and FOUR scores were comparable in bivariate associations with long-term outcome. Discharge coma scores performed best for both tools, with GCS discharge scores predictive in multivariate models.